Global Value Chains Meet Innovation Systems: Are There Learning Opportunities for Developing Countries? - Pietrobelli, Carlo; Rabellotti, Roberta (World development, 2011)
The Innovation Systems (IS) literature tends not to emphasize the crucial impact of international knowledge and innovation exchange and collaboration through, for example, inter-firm and intra-firm networks and Global Value Chains (GVC). In developing countries this aspect is crucial, with integration in GVC playing a growing and very important role in accessing knowledge and enhancing learning and innovation. However, there is no agreement in the literature about how innovation systems and GVC interact, and how this interaction is likely to affect enterprise learning. Three main conclusions emerge from the theoretical analysis and evidence presented in this paper. First, learning mechanisms can vary widely within the various forms of governance of GVC: they can be the result of the pressure to achieve international standards, or be facilitated by direct involvement of the value chain leaders when the suppliers’ competence is low and the risk of failure to comply is high. When the competences of the actors in the value chain are complementary, learning is mutual and is based on intense face-to-face interactions. Second, as we “open” IS to foreign sources of knowledge, the relationship between GVCs and IS is nonlinear and endogenous, and mutually affecting. On the basis of our model, we would expect a well-structured and efficient innovation system would help to reduce transaction complexity and enable transactions based on relational forms of GVC governance. Third, the internal governance of GVC is a dynamic phenomenon that is subject to continuous adjustments and changes, and the nature of the IS affects this co-evolution.